Combined effects of lactotripeptide and aerobic exercise on cognitive function and cerebral oxygenation in middle-aged and older adults. Issue 2 (9th January 2019) - Hamasaki, Ai; Akazawa, Nobuhiko; Yoshikawa, Toru; Myoenzono, Kanae; Tanahashi, Koichiro; Sawano, Yuriko; Nakata, Yoshio; Maeda, Seiji
ABSTRACT: Background: Age-related declines in cognitive function and cerebral perfusion increase the risk of dementia. Although nutrition and exercise may be effective in reducing cognitive decline, the effect of lactotripeptide (LTP) on cerebral oxygenation and hemodynamics remains unclear. Objectives: The aim of this study was to investigate the effects of LTP ingestion on cerebral oxygenation, cognitive function, and vascular function in middle-aged and older adults with or without an exercise intervention. Methods: We recruited 2 separate groups of participants, one with and one without an exercise intervention. Each group was then randomly assigned into a placebo group and an LTP group. The participants ingested a placebo or LTP every day. The exercise group performed aerobic exercises 4–6 d/wk. Before and after the 8-wk intervention, we measured oxygenated hemoglobin (oxy-Hb) concentration (oxy-Hb change) in the prefrontal cortex during the Stroop task (primary outcome), Stroop interference time, and carotid artery β-stiffness (both secondary outcomes). Results: Sixty-four participants completed the study. Changes in oxy-Hb signal in the prefrontal cortex were greater in the LTP group than in the placebo group under both the exercise and nonexercise conditions ( P  < 0.05). In addition, the magnitude of improvement in the oxy-Hb change in the left prefrontal cortex was correlated with Stroop interference ( r  = −0.39, P  < 0.05) and carotid β-stiffness ( r  = −0.41, P  < 0.05). Conclusions: An 8-wk intake of LTP increased cerebral oxygenation in the prefrontal cortex region in middle-aged and older adults, with and without exercise. The intervention-induced improvements in brain neural activation were associated with cognitive and vascular function. This trial was registered at www.umin.ac.jp as UMIN000022313.